Clinical features and cognitive impairments in children with frontal lobe epilepsy comorbid with attention deficit hyperactivity disorder - ZENG Xiaolu, ZHANG Jingwen, ZHANG Huiqiong, GUI Juan, REN Yuan, SUN Yueyu, ZENG Hanshi (Xin yixue)
Objective To investigate the clinical characteristics and cognitive impairments in children with frontal lobe epilepsy （FLE） comorbid with attention deficit hyperactivity disorder （ADHD） who have normal intelligence. Methods A total of 167 children aged 6-14 years， diagnosed with FLE at Guangdong Provincial People’s Hospital from January 2018 to June 2024， were screened for comorbid ADHD. They were divided into the FLE group and the FLE+ADHD group. Additionally， 72 children with ADHD alone and 74 healthy children of the same age from the child health clinic were included as the ADHD group and the healthy control group， respectively. The assessment results of the Wechsler Intelligence Scale for Children-Fourth Edition （WISC-IV） and the Wisconsin Card Sorting Test （WCST） were compared among the four groups. Clinical characteristics were compared between the FLE group and the FLE+ADHD group. Results Among the 167 FLE children， 62 （37.1％） cases met the diagnostic criteria for ADHD， with the inattentive subtype being the most common （68.3%）. Compared with the healthy control group， the FLE+ADHD group， the FLE group， and the ADHD group exhibited decreased scores in verbal comprehension index （VCI）， perceptual reasoning index （PRI）， working memory index （WMI）， processing speed index （PSI） and full-scale intelligence quotient （FSIQ）， alongside a lower score of WCST categories completed， and higher scores of WCST responses errors， perseverative responses errors， and non-perseverative responses errors （all P < 0.05）. Compared with the FLE group， the FLE+ADHD group demonstrated significantly lower VCI， PRI， WMI， PSI， FSIQ scores， lower score of WCST categories completed， and higher scores of WCST responses errors and perseverative responses errors （all P < 0.05）. Compared with the ADHD group， the FLE+ADHD group had lower VCI， PRI， FSIQ scores， and higher scores of WCST responses errors and non-perseverative responses errors （all P < 0.05）. Early onset of epilepsy （<6 years）， incomplete seizure control， use of multiple antiepileptic drugs， and interictal discharges on the left or bilateral sides on EEG were correlated with ADHD comorbidity. Conclusions Compared with children with FLE or ADHD alone， those with FLE and comorbid ADHD exhibit similar domains of cognitive impairment but show greater severity in some of these domains.